Age-dependent manifestations and case definitions of paediatric Zika: a prospective cohort study. Issue 3 (March 2020) - Burger-Calderon, Raquel; Bustos Carrillo, Fausto; Gresh, Lionel; Ojeda, Sergio; Sanchez, Nery; Plazaola, Miguel; Katzelnick, Leah; Mercado, Brenda Lopez; Monterrey, Jairo Carey; Elizondo, Douglas; Arguello, Sonia; Nuñez, Andrea; et al.
Summary: Background: Paedeatric Zika remains an understudied topic. WHO and the Pan American Health Organization (PAHO) Zika case definitions have not been assessed in children. We aimed to characterise clinical profiles and evaluate the diagnostic performance of the WHO and PAHO case definitions in a large cohort of paediatric Zika cases. Methods: From January, 2016 to February, 2017, encompassing the major 2016 Zika epidemic, participants in the Pediatric Dengue Cohort Study (PDCS) in Managua, Nicaragua, were encouraged to visit the study health centre at first indication of any illness. PDCS participants were aged 2–14 years, healthy at enrolment, and recruited before the initiation of the present study. Molecular and serological assays were used to test participants exhibiting any of four broad clinical profiles suspected of resulting from a symptomatic Zika virus infection. These clinical profiles were: fever and at least two of headache, retro-orbital pain, myalgia, arthralgia, rash, haemorrhagic manifestations, and leukopenia; fever and at least two of nausea or vomiting, rash, aches and pains, positive tourniquet test, leukopenia, and any dengue warning sign; undifferentiated fever without evident cause, with or without any other clinical finding; and afebrile rash with or without any other clinical finding. We characterised acute clinical findings (signs, symptoms, and complete blood counts) in both Zika cases and non-Zika cases. Findings: We prospectively followed a cohort of about 3700 children, of which 1110 were deemed eligible for inclusion. Four participants with laboratory-confirmed Zika (three co-infections with dengue virus, one missing complete blood count data) and two participants who were non-Zika cases (missing complete blood count data) were excluded from analysis. We analysed 556 laboratory-confirmed Zika and 548 non-Zika cases. The WHO case definition captured 176 confirmed Zika cases, and the PAHO definition 109 confirmed Zika cases, who presented with the most clinical findings and a dengue-like clinical profile. The remaining two thirds of Zika cases, principally characterised by undifferentiated fever or afebrile rash, were missed. Among Zika cases, rash (n=440)—particularly generalised erythematous rash (n=334)—fever (n=333), leukopenia (n=217), and headache (n=203) were most common and peaked within 3 days of illness onset. The most common Zika presentation over the first week of illness was rash only (n=80). The sensitivity of Zika case definitions increased across paediatric age (from 11·3% to 56·1% for the WHO case definition and from 6·0% to 36·6% for the PAHO case definition), as the prevalence of most clinical findings (particularly arthralgia) increased with age, irrespective of previous dengue virus infection. Consequently, Zika manifested differently across paediatric age; older Zika cases presented with a dengue-like clinical profile while younger Zika cases presented with undifferentiated fever or afebrile rash. Interpretation: We provide the most thorough description of paediatric Zika to date. Most paediatric Zika cases go undetected under the WHO and PAHO case definitions, suggesting that current standards for Zika case ascertainment require revision. Zika manifests with mild but differing clinical profiles across paediatric age, presenting major challenges to diagnosis, surveillance, and efforts to control future Zika epidemics. Funding: US National Institutes of Health.